Optimal Grounding Grid Design for Substaion and its Analysis - Soni, M.; George, Abraham (Asian Journal of Electrical Sciences, 2018)
Grounding grid design of the substation is essential to reducing grounding potential rise hence touch voltage inside the substation to safe guard the works of the substation and substation equipment. The grounding grid performance is affected by many factors such as soil resistivity, depth of the burial, conductor spacig, vertical ground rods and fault current. MATLAB programme is developed to analyse the gounding grid with all factors affecting it and results are shown by plotting the graphs , MATLAB progrmme is tested for refelection factor (k) greater than zero and lesser than zero. Using the programme developed one optimal solution is obtained out of many feasible solution.